(untitled) (Journal of Architectural Design, 2022)
The article highlights the importance of teaching the subject "Landscape architecture" in the context of the transition to the implementation of the planned tasks in the light of the Decree of the President of the Republic "Strategy of movements for the further development of the Republic of Uzbekistan"